Nurturing Independence: Parents as Game Changers for Children with Special Needs at Zamzam Kindergarten - Fitriani, Fitriani; Panji Yudha, Rivo (Seulanga : Jurnal Pendidikan Anak, 2025)
Children with special needs often face various challenges in developing independence, such as maintaining personal hygiene, dressing themselves, and performing other daily activities. This study aims to examine the role of parents in supporting the development of independence in children with special needs at Zamzam Kindergarten. The method employed is qualitative, with data collection techniques including interviews, observations, and document studies, as well as triangulation to ensure the validity of the findings. The results of the study highlight the role of guidance, familiarization with simple activities, and motivation provided by parents in enhancing children's independence. However, time constraints and a lack of parental knowledge base remain the pivotal challenges. Collaboration between parents and the school, such as through parenting classes, has proven effective in supporting children's independence development. These findings emphasize that synergy between parents and the school is key to optimally fostering independence in children with special needs.